EEG-Driven Prediction Model of Oxcarbazepine Treatment Outcomes in Patients With Newly-Diagnosed Focal Epilepsy - Wang, Bin; Han, Xiong; Zhao, Zongya; Wang, Na; Zhao, Pan; Li, Mingmin; Zhang, Yue; Zhao, Ting; Chen, Yanan; Ren, Zhe; Hong, Yang (Frontiers in Medicine, 2022)
Objective: Antiseizure medicine (ASM) is the first choice for patients with epilepsy. The choice of ASM is determined by the type of epilepsy or epileptic syndrome, which may not be suitable for certain patients. This initial choice of a particular drug affects the long-term prognosis of patients, so it is critical to select the appropriate ASMs based on the individual characteristics of a patient at the early stage of the disease. The purpose of this study is to develop a personalized prediction model to predict the probability of achieving seizure control in patients with focal epilepsy, which will help in providing a more precise initial medication to patients. Methods: Based on response to oxcarbazepine (OXC), enrolled patients were divided into two groups: seizure-free (52 patients), not seizure-free (22 patients). We created models to predict patients’ response to OXC monotherapy by combining EEG complexities and fifteen clinical features. The prediction models were gradient boosting decision tree- Kolmogorov complexity (GBDT-KC) and gradient boosting decision tree- Lempel-Ziv complexity (GBDT-LZC). We also constructed two additional prediction models, support vector machine- Kolmogorov complexity (SVM-KC) and SVM-LZC, and these two models were compared with the GBDT models. The performance of the models was evaluated by calculating the accuracy, precision, recall, F1-score, sensitivity, specificity and area under the curve (AUC) of these models. Results: The mean accuracy, precision, recall, F1-score, sensitivity, specificity, AUC of GBDT-LZC model after five-fold cross-validation were 81%, 84%, 91%, 87%, 91%, 64%, 81%, respectively. The average accuracy, precision, recall, F1-score, sensitivity, specificity, AUC of GBDT-KC model with five-fold cross-validation were 82%, 84%, 92%, 88%, 83%, 92%, 83%, respectively. We used the rank of absolute weights to separately calculate the features that have the most significant impact on the classification of the two models. Conclusion: 1) The GBDT-KC model has the potential to be used in the clinic to predict seizure-free with OXC monotherapy. 2). EEG complexity, especially Kolmogorov complexity may be a potential biomarker in predicting the treatment efficacy of OXC in newly diagnosed patients with focal epilepsy.